Filozofia prawa – przedmiot, funkcje i znaczenie społeczno-kulturowe - Wójtowicz, Ryszard (Człowiek i Społeczeństwo, 2015)
This article is an attempt to answer the question of: what is philosophy of law? What is philosophical reflection on law? What is the relation between the reflection on law and law “itself”? When defining philosophy of law I share the view that in the definition philosophy is genus proximum, whereas law is differentia specifica. The functions of philosophy of law are manifested in the social and cultural reality and depend on, among others, which sphere of man’s activity they are connected with. One of the functions is putting the ‘theory’ into practice, usage, legal practice, and rule-making because of the ideal of justice. However, the importance of philosophy of law can be expressed by the thesis: of inseparability of two values: freedom and law, because in philosophy of law understood as this (in the spirit of I. Kant’s philosophy), only law can guarantee freedom, thus the freedom of an individual assumes the existence of law, acceptation of law in all spheres of man’s activity in culture.